Combined approach of FT‐Raman, SERS and IR micro‐ATR spectroscopies to enlighten ancient technologies of painted and varnished works of art1. (12th August 2014) - Daher, Céline; Drieu, Léa; Bellot‐Gurlet, Ludovic; Percot, Aline; Paris, Céline; Le Hô, Anne‐Solenn; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> The characterization of materials involved in painted works of art provides a better knowledge of artworks through the understanding of artistic and technological processes. In this study, some pieces selected from a large corpus of French Decorative Arts objects from 18th century museum collections were analyzed. These materials are complex system made of a multilayered colored background, covered with varnish layers. Colored or gilded ornaments are applied, representing different characters, flowers or landscapes, then varnished again. The aim of this study was to improve the painting and varnishing techniques knowledge in the Decorative Arts field during the 18th century. Vibrational spectroscopies, Raman, surface enhanced Raman spectroscopy (SERS) and infrared, were used to analyze some specific parts of these objects, especially organic materials such as lake pigments, binders and varnishes, and some of them were identified. For this purpose, a set of experimental setups and parameters were used according to the samples. The performed analyses were thus done using conventional FT‐Raman at 1064 nm, SERS with a 458 nm excitation wavelength, infrared using a micro‐ATR mode, and by defining for each technique and each analysed sample the best set of analytical parameters. The results obtained are all complementary and allowed us to completely identify and characterize multilayered paint systems as well as varnish compositions using specific data treatment methodology. This study is a description of the various possibilities that vibrational spectroscopies can provide when the right settings are employed, with a deeper look into the vibrational features using new data treatments. Copyright © 2014 John Wiley & Sons, Ltd.